2006
DOI: 10.1038/nm1520
|View full text |Cite
|
Sign up to set email alerts
|

CD8+ T-cell responses to different HIV proteins have discordant associations with viral load

Abstract: Selection of T-cell vaccine antigens for chronic persistent viral infections has been largely empirical. To define the relationship, at the population level, between the specificity of the cellular immune response and viral control for a relevant human pathogen, we performed a comprehensive analysis of the 160 dominant CD8(+) T-cell responses in 578 untreated HIV-infected individuals from KwaZulu-Natal, South Africa. Of the HIV proteins targeted, only Gag-specific responses were associated with lowering viremi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

110
965
10
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 925 publications
(1,093 citation statements)
references
References 48 publications
110
965
10
2
Order By: Relevance
“…4C to F), with bVC groups possessing significantly broader Gag than Nef responses. Taken together, these observations are consistent with previous findings indicating that broad targeting of Gag but not Nef may contribute to HIV control among viremic controllers (4,(38)(39)(40).…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…4C to F), with bVC groups possessing significantly broader Gag than Nef responses. Taken together, these observations are consistent with previous findings indicating that broad targeting of Gag but not Nef may contribute to HIV control among viremic controllers (4,(38)(39)(40).…”
Section: Resultssupporting
confidence: 92%
“…We demonstrated that virologic control in subjects with protective HLA class I alleles was associated with greater breadth of CD8 ϩ T cell responses to Gag, consistent with previous data on the importance of Gag-specific responses in chronic HIV infection (4,38). In addition, we observed a bias toward targeting of greater breadth of HIV Gag epitopes compared to Nef indepen- dently of protective HLA class I allele expression among controllers.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…5867 Failure to contain viral replication in macaques correlated with the emergence of viral mutants that escaped from CTL immune surveillance. 68 , 69 In humans, CD8 + T cells targeting Gag are inversely associated with virus load, 70 including in long-term non-progressors, 71 and Gag T cell breadth has been associated with reduced plasma viremia. 72 …”
Section: Introductionmentioning
confidence: 99%